Digital Human Resources Supply Chain for Standardization of Human Resources Competence in Creative Industry of Tasikmalaya City - Karmila, Mila; Barlian, Barin; Yuni, Nurna; Firmansyah, Hary; Safitri, Egi Dia; Nurulaida, Rida (Journal of Business Management Education (JBME), 2024)
Digital technology is now a major factor in supporting HR development in the creative industry sector. Through the concept of Digital Human Resources Supply Chain (DHRSC), companies can utilize digital technology to manage the HR supply chain, from recruitment, skills development, to performance evaluation. This study uses a descriptive quantitative method approach that describes the phenomena that occur related to the implementation of Digital Human Resources Supply Chain (DHRSC) in the standardization of human resource (HR) competencies in the creative industry totaling 39 MSMEs spread across 7 (seven) sub-districts in Tasikmalaya City. Data analysis uses Multiple Linear Regression with the Mix Method method. The results of the study show that the implementation of DHRSC has a significant impact on the standardization of HR competencies in the creative industry in Tasikmalaya City. The main factors that influence this process are the use of digital technology, digital-based training, infrastructure availability, and government support